PENERAPAN KONSEP â€œ5Sâ€ DALAM UPAYA MENCIPTAKAN LINGKUNGAN KERJA YANG ERGONOMIS DI STIA LAN BANDUNG - Teni Listiani (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
An organization could increase its employeeâ€™s productivities through various approaches. One of them is through the ergonomic approach. In this approach, it is important to harmonize the employees with their working environment so that it may create security and working satisfaction. As a result, it will contribute to increasing productivity. Security and satisfaction in the work place can be achieved through the implementation of 5S concept (Seiri, Seiton, Seiso, Seiketsu and Shitsuke). It is a simple concept. However, putting it into practice needs awareness, discipline and high commitment from every employee.